Operation monitoring using JVAnalys - Stenmark, Johan (2004)
Train delays are an important issue for owners of railroad networks since they can limit profits and increase costs. One way to reduce this problem is to predict delays caused by railroad damage, such as faulty switches and broken track sections. To be able to do this, one needs to understand why different problems occur, and which tendencies that can be interpreted as an indication of an upcoming failure. Operation monitoring is a new angle of approach for Banverket, the Swedish Railroad Administration, to enable planning and accomplishing a more effective maintenance on their infrastructure, regarding both performance and costs. As a result of this, JvtC at Luleå University of Technology have, by order of Banverket Norra Banregionen and Banverket Produktion Nord, been asked to evaluate and further develop Banverket's ongoing concentration on operation monitoring. JvtC stands for Järnvägstekniskt Centrum. Focusing on maintanence, economy and technology, JvtC runs applied research and development to make the railroad more efficient. There are two systems that gather information about the signaling equipment today. One of these is DISA, a PLC based measurement system developed by Banverket Consulting. It is currently being tested in Abisko. The other system is ARGUS, the operation management system of Banverket Region Norr. The purpose of this degree thesis was to create a common database from which operation monitoring data easily could be extracted for evaluation of data quality and benefits. Validerat; 20101217 (root)